Single-phase double-column oblique angle oval iron core magnetically controlled reactor - JIANG YUANHUA; ZHANG LIMING (2013)
A single-phase double-column oblique angle oval iron core magnetically controlled reactor is characterized in that iron cores utilizes single-phase iron cores, each iron core comprises two core columns, each reactor is composed of three groups of single-phase double-column iron cores, the main iron core column is connected with an upper-lower iron yoke into a whole, the joint of the main iron core column ad the upper-lower iron yoke is an inclined joint, and the main iron core column is ladder-shaped multi-level section which is oval. By means of the special iron core structure, controllable silicon connected with a coil of the single-phase double-column oblique angle oval iron core magnetically controlled reactor is respectively triggered and communicated in a period of power voltage, and therefore a circulate loop is provided for controlling magnetic flow to enable the work main iron core column to be saturated. By regulation of a controllable silicon communication angle, volume and corresponding iron core